2019
DOI: 10.1071/rd18361
|View full text |Cite
|
Sign up to set email alerts
|

Role of maternal interleukin-8 (IL-8) in normal-term birth in the human

Abstract: Cytokines are the main factors involved in the normal functions of the placenta and delivery process. The aim of this project was to compare serum levels of interleukin-8 (IL-8), IL-6, tumour necrosis factor α (TNF-α) and transforming growth factor β (TGF-β) in term and prolonged-pregnancy mothers and their neonates. This study was performed on 240 participants including 60 term and prolonged-pregnancy neonates and their corresponding mothers. Serum levels of IL-8, IL-6, TNF-α and TGF-β were evaluated by the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
9
2
Order By: Relevance
“…One reason may be the seemingly chaotic cytokine expression and immunological regulation in late term pregnancies. In contrast to our results of cytokine upregulation in late term pregnancies, decreased or unchanged levels of IL-6, IL-8 and TNF-α has been associated with prolonged pregnancy ( 88 ), including all pregnancies beyond 40 +0 weeks. However, IL-8 was related to the induction of labor, consistent with our findings ( 88 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…One reason may be the seemingly chaotic cytokine expression and immunological regulation in late term pregnancies. In contrast to our results of cytokine upregulation in late term pregnancies, decreased or unchanged levels of IL-6, IL-8 and TNF-α has been associated with prolonged pregnancy ( 88 ), including all pregnancies beyond 40 +0 weeks. However, IL-8 was related to the induction of labor, consistent with our findings ( 88 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results of cytokine upregulation in late term pregnancies, decreased or unchanged levels of IL-6, IL-8 and TNF-α has been associated with prolonged pregnancy ( 88 ), including all pregnancies beyond 40 +0 weeks. However, IL-8 was related to the induction of labor, consistent with our findings ( 88 ). Most of the cytokines of high importance to the prediction model have been related to preterm labor in earlier studies ( 89 ), indicating that this cytokine pattern is associated with labor regardless of when in pregnancy the labor takes place.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we also observed a trend towards longer telomeres in placentas from women carrying a female. Moreover, we observed higher placental new-born weight ratio and fibroblast growth factor 2 in female’s placentas, which could indicate lower placenta ageing and a greater placental functional volume, with greater villous, angiogenesis and overall development, 37 , 38 as reported for placentas exposed to maternal exercise. 39 , 40 In agreement with our findings, Pac-Kożuchowska et al 8 also described greater placental-foetal weight ratio in females.…”
Section: Discussionsupporting
confidence: 61%
“…Further research on the specific inflammatory interactions associated with the onset and progression of parturition could lead to a better risk assessment and treatment of PTL. For instance, tracking IL-8 serum levels in pregnant women is suggested as a main marker to determine the time of parturition [ 104 ]. In addition, the maternal IL-6 and IL-8 serum levels are also considered as appropriate markers for monitoring the effects of tocolytics in PTL [ 105 ].…”
Section: Il-6 and Il-8 In A Healthy Pregnancymentioning
confidence: 99%